The Impact of Training Development, Work Environment, Motivation and Competency on Employee Performanve: Mediated by Job Satisfaction A Case Study of PT Adhi Karya (Persero) Tbk DPKA - Meidhy Panginda Saputra; Leonnard Ong (PT. Publikasiku Academic Solution, 2024)
With job satisfaction acting as a mediating variable, this study examines how employee performance is influenced by training development, work environment, motivation, and competence. Employees of PT. Adhi Karya,Tbk DPKA were given questionnaires as part of the data collection process. This study's sample consisted of 59 respondents who were selected using a proportionate and cluster sampling technique. Convergent validity, discriminant validity, composite reliability, Average Variance Extracted (AVE), Collinearity Statistics (VIF), path coefficient test, bootstrap test, and Structural Equation Modelling (SEM) test were all used to examine the data after it was processed using Smart PLS. This study indicates that motivation and training development have a positive and significant impact on job satisfaction. Job satisfaction is negatively and not significantly impacted by the work environment and skills. Additional findings show that while job satisfaction can influence employee motivation and training development, it cannot influence the work environment or competence. This research is expected to be an additional reference for company to improve quality in terms of employee performance. This research is extraordinary, for the sake of improvement in the future.